Ten simple rules for switching from face-to-face to remote conference: An opportunity to estimate the reduction in GHG emissions - Guignon, Valentin; Breton, Catherine; Mariette, Jérôme; Sabot, François; Fumey, Julien; Lefort, Vincent; Fiston-Lavier, Anna-Sophie (Public Library of Science, 2021)
In the context of wolrd pandemics, many face-to-face conference are to be canceled in profit or virtual ones. This publication propose ten simple rules and many other recommandations in order to turn a face-to-face conference into a remote virtual one and take into account the GHG emission reduction.